Trade Unions and “Europe”: Are the Members Out of Step? - Hyman, Richard (Relations industrielles / Industrial Relations, 2010)
In 2005 the “Constitutional Treaty” designed to restructure the governance of the European Union (EU) was rejected in popular referendums in France and the Netherlands. Subsequently only in Ireland was a referendum held on the Lisbon Treaty, which reinstated most elements in the previous version, in June 2008. Again a negative result threw the EU into crisis, though a second Irish vote in October 2009 yielded a different result.The “no” votes reflected a familiar pattern of popular rejection of initiatives on European integration. This article provides an overview of such referendums in western Europe, focusing in particular on the role of national trade unions in popular votes on EU accession and on Treaty revisions. It discusses trade union intervention in a dozen countries which held referendums since the Single European Act in the 1980s (and in the United Kingdom, which did not).It is evident that while mainstream trade unions (or at least their leaders) have usually endorsed the integration process, in most countries where referendums have been held their members have voted otherwise. This has been particularly evident among manual workers. Sometimes popular attitudes have been strongly influenced by narrowly nationalistic arguments, but rejection has often been based on “progressive” rather than “reactionary” grounds. In particular, the justified view that the EU in its current direction is encouraging a neoliberal, pro-capitalist drift in social and economic policy has underlain a left-wing critique of further integration.But having assented to the underlying architecture of actually existing Europeanization, unions have rarely shown the will to mobilize offensively around an alternative vision of social Europe. This has left the field open to right-wing nationalists (and to fringe left-wing parties with only a limited electoral base) to campaign in the “no” camp during referendums. Popular attitudes are malleable, but it requires a major strategic re-orientation if unions are to reconnect with their members in order to build a popular movement for a genuinely social Europe.